(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The philosopher, who conducts his research in the field of understanding social reality, is faced with the necessary questions about the foundations of the formation, the essence, the laws, the driving forces and the direction of social processes. The purpose of this study is analyze of the potential of the concepts of social process for understanding modern global politics on the basis of the history of philosophy. Such an analysis is necessary, as it determines the position of the researcher, his way of entering into the study material. The authors conclude on the content of the term «globalization». They give the following definition: «globalization» – a concept that is abstract and does not capture the essence of social contradictions, focusing on the scale of social processes. The significance of this conclusion is important for the self-reflection of the researcher of global processes. He should remember about the inadmissibility of substitution of the tasks of explanation and for the transformation of society by description or legitimization of the status quo. This approach gives us an opportunity to explain the global processes of modern social reality, to form adequate forecasts and programs of correction of the existing state of affairs in almost any sphere of public life. Key words: social process, philosophical history, global processes, globalization, fundamentals.